Thrombosis with thrombocytopenia after first dose of ChAdOx1 nCoV-19 vaccine: a case report - K. Kolodynskaja; S. Stankevičiūtė; A. Krikščionaitienė; N. Balčiūnienė (Neurologijos seminarai)
More than 5 billion vaccine doses against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) have been administered worldwide. In Lithuania, more than 1.72 million people have been vaccinated with at least one vaccine dose. Vaccines against SARS-CoV-2 are considered to be safe and effective measures to cope with COVID-19 pandemic. However, several cases of acute thrombotic events with thrombocytopenia after receiving ChAdOx1 nCoV-19 (AstraZeneca (Vaxzevria)) vaccine have been published. We report findings in one patient who presented with cerebral venous sinus thrombosis, intracerebral hemorrhage, and thrombocytopenia which occurred 12 days after receiving the first dose of ChAdOx1 nCoV-19 vaccine. The patient complained of headache and pain in the right eye, nausea, vomiting, and subfebrile fever. After deterioration of the state of consciousness, CT scan of the head showed a massive intracerebral hemorrhage, and laboratory tests revealed severe thrombocytopenia, high D-dimer level, and a low fibrinogen concentration. On the basis of clinical, laboratory and radiological findings, as well as the presence of antibodies to platelet factor 4 (PF4), the vaccine-induced immune thrombotic thrombocytopenia (VITT) was confirmed. After surgery and therapy with high doses of intravenous immunoglobulin, methylprednisolone and non-heparin anticoagulants, the patient’s clinical condition and laboratory parameters improved.